2022
DOI: 10.1007/s10311-022-01387-z
|View full text |Cite
|
Sign up to set email alerts
|

Metal–organic frameworks for active food packaging. A review

Abstract: Food wastage is a major concern for sustainable health and agriculture. To reduce food waste, classical preservation techniques such as drying, pasteurization, freeze-drying, fermentation, and microwave are available. Nonetheless, these techniques display shortcomings such as alteration of food and taste. Such shortcomings may be solved by active food packaging, which involves the incorporation of active agents into the packaging material. Recently, metal–organic frameworks, a class of porous hybrid supramolec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 169 publications
1
25
0
Order By: Relevance
“…235 Studies have found that ZnO NPs can induce a toxic effect on aquatic and terrestrial species even with concentration as low as 1 mg/L. 236 ZnO NPs are considered biodegradable nanoparticles. 237 The three main hazardous effects of ZnO NPs include toxicity, genotoxicity, and carcinogenicity.…”
Section: Safety Aspect Of Use Of Zno Nps In Food Packagingmentioning
confidence: 99%
“…235 Studies have found that ZnO NPs can induce a toxic effect on aquatic and terrestrial species even with concentration as low as 1 mg/L. 236 ZnO NPs are considered biodegradable nanoparticles. 237 The three main hazardous effects of ZnO NPs include toxicity, genotoxicity, and carcinogenicity.…”
Section: Safety Aspect Of Use Of Zno Nps In Food Packagingmentioning
confidence: 99%
“…Antioxidant activity in these types of active food films has mainly been focused on limiting or delaying lipid and protein oxidation. Unlike typical food packaging materials, active food packaging methods have adequate barriers against H 2 O and O 2 , humidity absorbers, flavor, carbon dioxide absorbers or emitters, ethylene gas (such as ethylene absorbers/oxidizing agents), antioxidation materials, and antimicrobial agents [49][50][51][52][53][54]. Depending on the functional elements set in the biopolymers, the packaging can offer biological activities for the packaged foods, such as antioxidant and antimicrobial shields [55].…”
Section: Active Food Packagingmentioning
confidence: 99%
“…Because of metal–organic frameworks’ unique and intriguing structural properties, their synthesis has attracted considerable scientific attention during the last two decades in different scientific fields, as presented in Fig. 1 (Sultana et al 2022 ; Kreno et al 2012 ; Kaur et al 2016 ). For example, capsaicin hydrophobicity was significantly regulated after being loaded in Fe III -hollow metal–organic framework-5, and the phase separation problem was effectively solved by Fe III -hollow metal–organic framework-5.…”
Section: Metal–organic Frameworkmentioning
confidence: 99%
“…Due to the extraordinary physical and chemical properties of metal–organic frameworks, such as their high surface areas, tunable pore sizes, and elastic internal surface properties, metal–organic frameworks have attracted a great deal of researchers’ attention in various applications as presented in Fig. 1 (Zhou and Kitagawa 2014 ; He et al 2019a ; Sultana et al 2022 ). Fields among these applications are sensors (Kreno et al 2012 ; Wang et al 2021a ), catalysts for organic transformations (Guo et al 2021 ), biomass conversion (Guo et al 2021 ; Osman et al 2021a ), photovoltaic (Kaur et al 2016 ), electrochemical applications (Xiao et al 2020 ), gas storage and separation (Li et al 2018 ), photocatalysis (Dhakshinamoorthy et al 2018 ), and biomedical applications (Yang and Yang 2020 ).…”
Section: Introductionmentioning
confidence: 99%